Local Wisdom Inheritance Strategy in Reog Ponorogo Artistry - Queenie Ummu A'yunin*; Riadi Syafutra Siregar (Universitas Syiah Kuala, 2024)
Local wisdom in Reog Ponorogo art is important to preserve and pass on to the next generation. The rapid influence of globalization and modernization brings many influences including external cultures that are not in accordance with the nation's culture. Inheritance is carried out by developing relevant strategies so that it becomes a sustainable process. This research uses qualitative methods with data collection techniques in the form of observation, interviews and documentation. The analysis technique used in this research uses the Miles and Huberman model, in the form of data reduction, data display and conclusionmaking. The results showed that the local wisdom inheritance strategy in the Reog Ponorogo art in Ponorogo Regency has been running by involving many elements of society, starting from the government, art actors and educational units through extracurricular activities.